On The Allocation of a Takeover Purchase Price under AASB1013 - Kieran James; Janice How; Peter Verhoeven (Asian Academy of Management Journal of Accounting and Finance, 2011)
The purpose of this paper is to document and explain the allocation of takeover purchase price to identifiable intangible assets (IIAs), purchased goodwill, and/or target net tangible assets in an accounting environment unconstrained with respect to IIA accounting policy choice. Using a sample of Australian acquisitions during the unconstrained accounting environment from 1988 to 2004, we find the percentage allocation of purchase price to IIAs averaged 19.09%. The percentage allocation to IIAs is significantly positively related to return on assets and insignificantly related to leverage, contrary to opportunism. Efficiency suggests an explanation: profitable firms acquire and capitalize a higher percentage of IIAs in acquisitions. The target's investment opportunity set is significantly positively related to the percentage allocation to IIAs, consistent with information-signalling. The paper contributes to the accounting policy choice literature by showing how Australian firms make the one-off accounting policy choice in regards allocation of takeover purchase price (which is often a substantial dollar amount) in an environment where accounting for IIAs was unconstrained.